Arab dentists' refusal to treat HIV positive patients: a survey of recently graduated dentists from three Arab dental schools. (4th July 2017) - Arheiam, Arheiam; El Tantawi, Maha; Al-Ansari, Asim; Ingafou, Mohamed; El Howati, Asma; Gaballah, Kamis; AbdelAziz, Wafaa
Abstract: Objective: To assess intended refusal of recent graduates from three Arab dental schools to treat HIV + patients and factors associated with this intention. Materials and methods: In 2015, convenience samples of recent dental graduates were included from Libya, Egypt and the United Arab Emirates. Participants responded to a questionnaire assessing personal background, knowledge of oral manifestations and fluids transmitting HIV, perceived adequacy of training and self-efficacy to manage blood exposures, attitude to risk of infection, moral beliefs and willingness to treat HIV + patients. Logistic regression assessed factors associated with intended refusal to treat HIV + patients. Results: The overall response rate was 552/710 (77.8%), mean age = 23.7 years with 41.8% males. The mean (SD) scores for knowledge of oral manifestations and fluids transmitting HIV were 5.5 (1.3)/8 and 4.2 (1.7)/7. The mean (SD) scores for attitude to risk of infection and moral beliefs were 2.9 (1.0)/4 and 2 (0.9)/3, respectively. One-third of respondents indicated intention to refuse treating HIV + patients. Knowledge of body fluids transmitting HIV and moral beliefs were associated with lower odds of refusing to treat HIV + patients (OR = 0.86 and 0.38) whereas attitude indicating greater concern for risk of infection was associated with higher odds (OR = 1.54). Conclusions: One third of dentists from three Arab dental schools indicated they would refuse to treat HIV + patients. Adequate knowledge and moral beliefs reflecting professional ethics were associated with lower odds of refusal counterbalancing the association with attitude indicating increased concern for risk of infection with implications for dentist education and training.